Salt tolerance of cowpea genotypes during seed germination and seedling growth: Salt tolerance in cowpea genotypes in Bangladesh (Journal of the Bangladesh Agricultural University, 2019)
Cowpea (Vigna unguiculata (L.) Walp.) is one of the most important grain legumes worldwide and its production is affected by increasing soil salinity due to global climate change. An experiment was conducted at the Plant Physiology Laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh to evaluate the germination capability of seven cowpea genotypes under salt stress. The germination test was carried out in Petri dishes following two factorial CRD with three replications. Seven cowpea genotypes viz, Red Pine, Green Super, Hai Jiang San Hao, Kegornatki, Kegornatki Green, Kegornatki HYV & Kegornatki Red; and three salt levels viz, 0, 6 & 12 dSm-1, were used as experimental treatments. The germination percentage (GP), mean germination time (MGT), radicle and plumule length, radicle and plumule fresh and dry weight and different stress tolerance indices were recorded to screen the genotypes for salt tolerance. The study highlighted that salt concentrations drastically reduced seed germination and significantly delayed the process in all genotypes. The GP, length and biomass of radicle and plumule and salt tolerance indices were significantly decreased while the MGT was significantly increased with increasing salt stress in all cowpea genotypes. A significant variation among the genotypes in response to salt stress was also observed. Among the seven cowpea genotypes, Hai Jiang San Hao and Green Super showed higher salt tolerance in comparison to the other genotypes based on the measured traits; these genotypes can be used for further breeding program and/or cultivation in coastal saline prone areas with further investigation.J. Bangladesh Agril. Univ. 17(1): 39–44, March 2019